Laminar burning velocity of natural gas/syngas-air mixture (2013)
This study suggests the equimolar mixture of Natural Gas (100% CH4) and Synthesis Gas (40% H2 + 40% CO + 20% CO2) as an alternative to reduce hydrocarbons consumption and reduce pollutant emissions. As a key parameter to characterize this combustible mixture, the laminar burning velocity was studied based on numerical simulations and experimental measurements in fl ames generated using a contoured slot-type nozzle burner and the Schlieren technique, varying the air-fuel ratio at standard temperature and pressure. It was found that the fl ame speed of the equimolar mixture increases with respect to that of pure methane. This behavior can be explained by the presence of hydrogen in the fuel mixture, which has a direct effect on the combustion kinetics, generating H and OH radicals that increase the global reaction rate of the mixture and consequently the burning velocity.